Um estudo sobre jovens e violência no espaço escolar - Salles, Leila Maria Ferreira [UNESP]; Silva, Joyce M. A. De Paula E [UNESP]; Castro, Juan Carlos Revilla; Fernandez Villanueva, Concepción (Associação Brasileira de Psicologia Social, 2014)
This paper is the result of a research project on the subject of youth, violence and school. The purpose of this project was to investigate the understanding of the young people on the violence in society, at school and in their own lives. The assumption is that knowing the aggressors' and victims' perspective about their experiences of violence helps to clarify the symbolic and the normative universes that rule violent conducts and the possible ways to reduce the incidence of violence. Data were collected through focus groups. One of the groups was composed by students qualified by their school's board as protagonists in situations of violence. The other group was consisted by those considered as good students. Data analysis shows the differences between the logic of violence at school, the school violence and violence against the school.

Este texto é resultado de um projeto de pesquisa sobre a temática do jovem, violência e escola. O objetivo desse projeto foi investigar a interpretação dos jovens sobre a violência na sociedade, na escola e na sua própria vida. O pressuposto é o de que conhecer a perspectiva de agressores e vítimas sobre as suas experiências de violência contribui para esclarecer os universos simbólicos e normativos que regulam as condutas violentas e as possíveis formas de reduzir sua incidência. Os dados foram coletados por meio de grupos focais. Um dos grupos foi constituído por alunos qualificados pela escola como protagonistas de situações de violência. O outro grupo foi constituído por jovens considerados bons alunos. A análise dos dados mostra uma diferença entre a lógica da violência à escola e da escola, e a violência na escola.

Este texto es el resultado de un proyecto de investigación sobre el tema de la violencia juvenil y la escuela. El objetivo de este proyecto fue investigar la interpretación de los jóvenes sobre la violencia en la sociedad, en la escuela y en su propia vida. El supuesto es que el conocimiento de la perspectiva de los agresores y de las víctimas acerca de sus experiencias de violencia ayuda a clarificar los universos normativos y simbólicas que regulan el comportamiento violento y las posibles maneras de reducir su incidencia. Los datos fueron recolectados a través de grupos de enfoque. Un grupo fue formado por la escuela calificada como protagonistas de los estudiantes situaciones de violencia. El otro grupo estaba formado por los jóvenes considerados buenos estudiantes. Análisis de los datos muestra una diferencia entre la lógica de la violencia hacia y desde la escuela y la violencia escolar.
Un estudio sobre juventud y violencia en la escuela
A study on youth and violence at school
Keywords: escola; violência; jovens; school; violence; youth